Simplified Modeling and Simulation of Electricity Production from a Dish/Stirling System - Mahamat Hassane Babikir; Venant Sorel Chara-Dackou; Donatien Njomo; Mahamat Barka; Mahamoud Youssouf Khayal; Daniel Roméo Kamta Legue; Jean Paul Gram-Shou (International Journal of Photoenergy)
This work is part of the dynamic of proposing a solution to the problem of access to electricity in Chad, which has a rate of access to electricity of 3%. N’Djamena has significant solar potential that can be harnessed to generate electricity. In this paper, we present a theoretical study of the performances of the Dish/Stirling system with the purpose of producing electricity, based on a mathematical model taking into account each of the subparts of the system (concentrator, solar cavity receiver, and Stirling engine). Hydrogen is preferred to helium as the working fluid for operating the Stirling engine at high temperatures. This coupled model made it possible to estimate the monthly average of the electric power produced by this modular system and also its overall solar electricity yield.